Kepemimpinan Pastoral untuk Remaja Awal di Era Digital - Hutabarat, Irene Christanti; Hutabarat, Juliaman; Aftur, Riska; Sianipar, Rikardo P. (Sekolah Tinggi Teologi Kharisma, 2025)
AbstractEarly adolescents face significant spiritual challenges due to digital exposure and dependence on gadgets. This study aims to develop a pastoral care model based on 1 Peter 5:2-3 that is relevant for adolescents in the digital age. Qualitative methods were used through semi-structured interviews and observations at the GBI Kampung Melayu, combined with historical-critical and canonical interpretation approaches. The results indicate that pastoral care based on example, relationships, and peer mentoring is more effective than an authoritative approach. Spiritual leaders must be present as living role models, not just doctrinal teachers. The use of Jesus' principles of service and biblical leadership values encourages the formation of a spiritual community that is adaptive to digital culture. This study contributes to the development of a contextual pastoral model that is relevant, participatory, and transformative in addressing the faith formation needs of adolescents in the digital age.AbstrakRemaja awal menghadapi tantangan spiritual signifikan akibat paparan digital dan ketergantungan pada gadget. Penelitian ini bertujuan mengembangkan model penggembalaan berdasarkan 1 Petrus 5:2-3 yang relevan untuk remaja era digital. Metode kualitatif digunakan melalui wawancara semi-terstruktur dan observasi di GBI Kampung Melayu, dikombinasikan dengan pendekatan tafsir historis-kritis dan kanonik. Hasil menunjukkan bahwa penggembalaan yang berbasis keteladanan, relasi, dan peer mentoring lebih efektif dibanding pendekatan otoritatif. Pemimpin rohani harus hadir sebagai teladan hidup, bukan hanya pengajar doktrinal. Penggunaan prinsip pelayanan Yesus dan nilai kepemimpinan Alkitabiah mendorong pembentukan komunitas rohani yang adaptif terhadap budaya digital. Penelitian ini memberikan kontribusi terhadap pengembangan model pastoral kontekstual yang relevan, partisipatif, dan transformatif dalam menjawab kebutuhan pembinaan iman remaja di era digital.